ANALISIS PERBEDAAN STANDARD OPERATING PROCEDURE (SOP) KERJA WAITER/SS SEBELUM DAN SESUDAH ADANYA PANDEMI COVID-19 DI TUK-TUK BALI RESTORAN - Mutria Farhaeni; A.A Ngurah Dyah Prami; I Komang Sagra Mita (Majalah Ilmiah Widyacakra, 2021)
ABSTRACTThe purpose of this study was to determine the Standard Operating Precedure forwaiter / ss work before and after the Covid-19 pandemic at Tuk-Tuk Bali Restaurant. Inthe world of tourism, temporary accommodation such as hotels and restaurants areneeded. The availability of tourism accommodation must be supported by the quality ofskilled and professional human resources in their respective fields. The Covid-19 casein Indonesia and even the world that is currently happening have forced restrictions oncommunity activities. With this new life order, this has an impact on the quality ofservice in all accommodation places, from food stalls to the tourism sector such ashotels, restaurants and other accommodation places. In the current life order, one mustalways prioritize common health and must comply with health protocols. The results ofthis research are in the form of changes to the standard operating procedures for workthroughout the company, one example is in Tuk-Tuk Bali restaurants, this change inStandard Operating Procedures is expected to maintain the health and safety ofemployees and restaurant visitors. This Standard Operating Procedure is made so thatcompanies can continue to operate during a pandemic. while still running healthprotocols. There is a change in the Standard Operating Procedure changes that occurin terms of grooming and welcoming procedures for visiting customers.Keywords: Standard Operating Procedure, Waiter / SS and Covid-19ABSTRAKSITujuan Penelitian ini bertujuan untuk mengetahui Standard Operating Precedure kerjawaiter/ss sebelum dan sesudah adanya pandemi covid-19 di Tuk-Tuk Bali Restoran.Ketersediaan akomodasi pariwisata harus didukung adanya kualitas sumber dayamanusia yang terampil dan profesional dalam bidangnya masing-masing. Kasus Covid19 di Indonesia bahkan dunia yang sekarang terjadi memaksakan adanya pembatasanaktivitas masyarakat. Dengan adanya tatanan kehidupan yang baru hal ini berdampakterhadap kualitas pelayanan di semua tempat akomodasi, mulai dari warung sampai kesektor pariwisata seperti hotel, restoran, dan tempat akomodasi lainnya. Dalam tatanankehidupan yang baru berjalan saat ini seseorang harus selalu mengutamakan kesehatanbersama dan wajib mematuhi protokol kesehatan. Hasil penelitian ini berupa perubahanStandard Operating Procedure kerja di seluruh perusahaan, salah satu contohnya diTuk-Tuk Bali restoran perubahan Standard Operating Procedure ini diharapkan dapatmenjaga kesehatan dan keselamatan karyawan dan pengunjung restoran, StandardOperating Procedure ini dibuat agar perusahan bisa tetap beroperasi dimasa pandemidengan tetap menjalankan protocol kesehatan. Adanya perubahan Standard OperatingProcedure perubahan yang terjadi dalam hal grooming dan tatacara penyambutanpelanggan yang berkunjung.Kata kunci: Standard Operating Procedure, Waiter/ss dan Covid-19